Radiation modification of polyethylene surgical implants - Podrez-Radziszewska, Marzena; Głuszewski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2005)
Modification of surgical implants using the example of radiation processing of polyethylene was discussed. Treatment of some polymer materials carried out in the course of radiation sterilization was described. Investigation results of mechanical properties of irradiated ultra high molecular weight polyethylene were considered in this work. Details of mechanical properties investigation results were skipped to underline significant conclusions from the medical point of view.